Challenges of Flood Management in the Bhutahi Balan (Water Nepal, 2004)
Several small rivers flow from Nepal into North Bihar. The rivers originate in the Chure range of Nepal. Bhutahi Balan is one such river, which is a tributary to the Kosi. Bhutahi Balan is ephemeral and comes to spate in the aftermath of rainfall in the catchment. The flood causes major devastation in its wake. This paper encapsulates the story of the river and the efforts to control it by building embankments. This response has neither ameliorated flooding nor brought security to the people. The paper suggests that more reflective analysis of the suitability of the technology via-a-vis the environment and society is needed.Water Nepal Vol.11, No.1, 2004, pp.29-49